Legal Regulation of Care for Mixed Marriages in Selected Central European Countries Comparison and Proposals = Régulations légales concernant les mariages mixtes dans l’Église catholique dans certains pays d’Europe centrale Comparaison et propositions = Regolamentazioni legali riguardanti i matrimoni misti nella Chiesa cattolica in alcuni paesi dell’Europa centrale Confronto e proposte - Němec, Damián (Ecumeny and law, 2023)
This article presents the modalities of legal regulation regarding mixed marriages in the Catholic Church in selected countries of Central Europe: Poland, the Czech Republic, the Slovak Republic, Germany, and Austria. In the comparative part, it presents a comparison of the solutions in the following areas: announcement before marriage, declaration before requesting permission for a mixed marriage, mandate for permission for marriage, dispensation from the canonical form and possibilities of access to the sacrament of the Eucharist in mixed marriages. In the synthesizing part, it presents not only an evaluation of the solutions described and suggestions for their improvement, but also the way in which the relevant regulations and forms are issued and published from the point of view of pastoral care and the openness of the Church. In the appendix, it discusses the legal solution to similar situations (marriage of a Catholic party with an unbaptized person and with a Catholic party distant from Christian faith and practice) and presents in a framework the draft directive of the Bishops’ Conference for mixed and similar marriages in the Czech Republic.